Tract based spatial statistic reveals no differences in white matter microstructural organization between carriers and non-carriers of the APOE ɛ4 and ɛ2 alleles in young healthy adolescents - Dell'Acqua, Flavio; Banaschewski, Tobias; Flor, Herta; Rietschel, Marcella (Journal of Alzheimer's disease, 2015)
The apolipoprotein E (APOE) ɛ 4 allele is the best established genetic risk factor for Alzheimer’s disease (AD) and has been previously associated with alterations in structural gray matter and changes in functional brain activity in healthy middle-a